Kontribusi Usaha Mikro Kecil dan Menengah: Pajak, Corporate Social Responsibility, Shodaqoh, dan Kebermanfaat Usaha - Suwarno Suwarno; Rahmawati Rahmawati; Sri Murni; Warsina Warsina (InFestasi, 2020)
The existence of Micro, Small, and Medium Enterprises (MSMEs), which constitute the largest share in the national economy, is an indicator of the level of community participation in various economic sectors. UMKM towards the environment that is approved by tax, alms, CSR, and business benefit. The method of analysis uses descriptive analysis. Data collection using observations, questionnaires, and direct interviews to 250 MSMEs engaged in batik and grocery stores in Surakarta. 66.8% MSMEs have not paid taxes and 33.2% MSMEs have paid taxes, 96.8% MSMEs in Surakarta have done shodaqoh, 60.8% MSMEs in Surakarta have not done CSR and 37.2% are actively doing CSRs, 85, 6% of MSMEs stated that their businesses provided benefits for the community, while for the community about the business environment. Other findings show that MSMEs who have paid business taxes are long-term business groups, have permanent businesses, and have large-scale relationships and most MSMEs do not do CSR more because they have not seen the benefits of CSR activities.